Angiographic Outcomes of Direct and Combined Bypass Surgery in Moyamoya Disease - Ge, Peicong; Ye, Xun; Liu, Xingju; Deng, Xiaofeng; Wang, Jia; Wang, Rong; Zhang, Yan; Zhang, Dong; Zhang, Qian; Zhao, Jizong (Frontiers in Neurology, 2019)
Objective: To identify associated risk factors for the angiographic outcomes after direct and combined bypass surgery in moyamoya disease (MMD). Methods: All direct and combined bypass procedures performed from June 2009 to May 2015 were screened in this prospective cohort study. Patients acquired presurgical and follow-up catheter angiography were included. Bypass patency and postoperative collateral formation were evaluated. Univariate and multivariate logistic regression analyses were performed to determine the influence factors for bypass patency and postoperative collateral formation. Results: In total, 188 consecutive bypass procedures were included. After an 18-moth median follow-up, the anastomosis patency rate was 88.3%. Postoperative collateral formation was associated with the patency of the anastomosis (Gamma=0.891, p<0.001 ). Multivariate logistic regression analysis showed that presence of hemorrhage (OR, 0.298; 95% CI, 0.125–0.709; p = 0.006) was associated with obstructed anastomosis. Among the 188 bypass surgery, 125 (63.2%) hemispheres had good postoperative collateral formation and 85 (36.8%) had poor postoperative collateral formation. Multivariate logistic regression analysis showed that younger age at operation (OR, 2.396; 95% CI, 1.231–4.664; p = 0.010) was associated with good postoperative collateral formation, while the poor postoperative collateral formation was related to presence of hemorrhage (OR, 0.329; 95% CI, 0.143–0.758; p = 0.009) and dilated anterior choroidal artery (OR, 0.472; 95% CI, 0.240–0.929; p = 0.030). Conclusions: This study has demonstrated that presence of hemorrhage predicts lower patency rates. Younger age at operation was associated with good postoperative collateral formation, while the poor postoperative collateral formation was related to presence of hemorrhage and dilated anterior.